CSR and GCG Effectivess on Financial Performance: Earnings Management as a Mediator - Nabillah, Azkatul; Bariyyah, Bikruniyatul; Yulianto, Agung; Fariani Siregar, Nelia (Journal of Accounting and Finance Management, 2025)
This investigation analyzes how the effectiveness Good Corporate Governance and Corporate Social Responsibility affects financial performance by considering the intermediary function of earnings management. Owned by the State businesses the Indonesia Stock Exchange lists those (IDX) are the subject of this quantitative analysis during the time frame 2020 to 2023 with a sample size of 13 Owned by the State businesses. The information utilized in this investigation are secondary, the use of purposeful sampling was the approach utilized to select the sample. The research findings show that the effectiveness of CSR and GCG through the audit committee and the board of commissioners has a significant positive impact on net income, but not on earnings management. In contrast, institutional ownership and independent commissioners have no significant effect on net income, and earnings management does not mediate the relationship between CSR and GCG effectiveness and financial performance. This suggests that companies that apply the principles of sustainability and transparency increase stakeholder trust and contribute positively to national economic stability and growth.